Fanny Kemble : A Performed Life - David, Deirdre, 1934- (Book collections on Project MUSE., 2007)
"Fanny Kemble played a highly significant cultural role on both sides of the Atlantic. As David so convincingly shows, the life of this actress-turned-writer-turned-polemicist not only offers a fascinating subject in its own right but also intersects with a host of nineteenth-century figures who still interest us today."--U.C. Knoepflmacher.